Reduced serum IgG galactosylation is associated with increased inflammation during relapses of neuromyelitis optica spectrum disorders - Gao, Shiyu; Jiao, Xin; Guo, Ruoyi; Song, Xiujuan; Li, Bin; Guo, Li (Frontiers in Immunology, 2024)
Background and Objective: Post-translational modifications of antibodies, with a specific focus on galactosylation, have garnered increasing attention in the context of understanding the pathogenesis and therapeutic implications of autoimmune diseases. However, the comprehensive scope and the clinical significance of antibody galactosylation in the context of Neuromyelitis Optica Spectrum Disorder (NMOSD) remain enigmatic.The primary aim of this research was to discern disparities in serum IgG galactosylation levels between individuals in the acute stage of NMOSD relapse and their age- and sex-matched healthy counterparts. Methods: A total of fourteen untreated NMOSD patients experiencing an acute relapse phase, along with thirteen patients under medication, were enrolled, and an additional twelve healthy controls of the same age and gender were recruited for this investigation. Western blot and lectin enzyme techniques were used to determine the level of IgG galactosylation in the serum samples from these subjects. The expression of CD45+, CD3+, CD3+CD4+, CD3+CD8+, CD19+, and CD16+CD56+ in peripheral blood leukocytes was measured by flow cytometry. The enzyme-linked immunosorbent assay (ELISA) was also used to quantify the amounts of cytokines. Robust statistical analysis was executed to ascertain the potential associations between IgG galactosylation and the aforementioned immune indices. Results: In the context of NMOSD relapses, serum IgG galactosylation exhibited a notable decrease in untreated patients (0.2482±0.0261), while it remained comparatively stable in medicated patients when contrasted with healthy controls (0.3625±0.0259) (p=0.0159). Furthermore, a noteworthy inverse correlation between serum IgG galactosylation levels and the Expanded Disability Status Scale (EDSS) score during NMOSD relapse was observed (r=-0.4142; p=0.0317). Notably, IgG galactosylation displayed an inverse correlation with NMOSD relapse among peripheral blood CD45+, CD3+, CD3+CD8+, CD19+ cells, as well as with IL-6 and IL-8. Nevertheless, it was not determined whether IgG galactosylation and CD3+CD4+ T cells or other cytokines are statistically significantly correlated. Conclusion: Our research identified reduced IgG galactosylation in the serum of NMOSD patients during relapses, significantly correlated with disease severity, thereby providing a novel target for the diagnosis and treatment of NMOSD in the realm of medical research.